Evaluation of the digital medicine perception by the youth consumer segment - Anna B. Tsvetkova; Anatoliy V. Shishkin (Статистика и экономика)
The purpose of the study is to assess the perception of various aspects of digital medicine by the youth segment of consumers, the degree of readiness to consume its services and the level of involvement in this process. The last few years have become a turning point for medicine, if we talk about the number of new directions, emerging techniques and the introduction of digital technologies. Digital medicine uses information and communication technologies to solve health problems of different groups of patients. Its capabilities help doctors and patients to analyze the development of the disease, calculate health risks. The segment of medical gadgets of digital medicine offers consumers a variety of products. Artificial intelligence and wearable devices are becoming common means of organizing the treatment process and monitoring the human condition. Young people, as a rule, more actively perceive any novelties and include еthem in their daily life. Is it really so? If we consider Russian young consumers, since foreign experience indicates their rather high interest.Materials and methods of research. The presented study of the perception of the youth audience and readiness to use digital medicine is based on the methodology, proposed by the venture Fund Rock Health, dedicated to digital health. This Fund conducts research, aimed at improving the quality, safety and accessibility of modern medicine. The study is conducted by online survey of consumers who have access to the Internet at home, at work or through cell phones. The questionnaire was adapted for the Russian target audience. The results of the research of the consulting company Accenture, which regularly studies the trends in the consumption of medical technologies with the use of artificial intelligence, robotics and gadgets for self-diagnosis, were used as a factual basis. Data of research of the analytical company CB Insights, forming annual forecasts about the changes in healthcare, and also materials of joint research of the company Econsultancy and the developer of IT technologies for medicine Adobe are considered. The article presents some data of the report of the American company Change Healthcare, which has a strategic partnership with Google Cloud.Results of the research on the one hand, show the high involvement of young people in the field of digital technologies. The survey includes 380 respondents, 89% are smartphone users and 83% regularly visit social networks. However, they are quite wary of digital medicine, requiring the control of personal data. They trust their doctor more than mobile apps and Internet resources; they are reluctant to buy wearables, little understanding of what is telemedicine. They are limited to searching for medical information on the Internet only about services, doctors, medicine and treatment technologies to find out general information.Conclusion. The content analysis shows that digital medicine is becoming a popular trend in the development of modern healthcare. New technologies are being introduced, the key areas of development of which are focused on the Internet of things for medicine (IoT), artificial intelligence, mobile apps, genome editing, telemedicine, blockchain projects and cloud computing. The Russian market is slowly developing. Young consumers are not yet active in the consumption of digital health services and products. The key reasons for this are low awareness of the benefits and concerns about the security of the personal data.